Reconsideration of Opening Design in the Integration of Natural Light into Interior Space - Naseri, Ouldouz (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: Natural light was the main lighting sources before the invention of artificial lamps. After that, most of the designers started to design windowless buildings, which caused the consumption of a lot of fossil fuel besides its expensiveness. After 1960s, some of the architects started to re-think about natural lighting. They started to consider natural lighting in their design until the contemporary period. During the contemporary period, a design event affects architecture and forced architects and designers to be part of it with the invention of new technologies or materials. Therefore, for instance, it led to the emergence of digital architecture, where parametric design or fluid design arose as a result. This kind of architecture allows architects to design in any form, shape, and size where the priority was the shelter and functional role of opening more than the interior and its effects on the user or space. Therefore, together with the form, changes on opening and fenestration design affected the integration of natural light into interior spaces as well. In due course, this study discourses the role opening design has on the integration of natural light into the interior space. It gives priority to the effects of opening on the interior space more than the shelter of a building or the functional role of the openings. Accordingly, at first, this study emphasizes the need for reconsideration of openings and investigates different methods and techniques that openings can be designed. Then it evaluates the effects of various opening designs on the integration, natural light into an interior space and its effects on interior design / space besides the user. Keywords: Natural Lighting, Interior Design, Interior Space, Opening and Fenestration Design, Opening Design Techniques, Interior Design Elements and Principles. ………………………………………………………………………………………………………………………… ÖZ: Yapay aydınlatmanın keşfinden once doğal ışık temel aydınlatma kaynağı idi. Yapay aydınlatma ile birlikte tasarımcılar penceresiz binalar tasarlamaya başladırlar. Bu pahalı bir çözüm olmakla birlikte, çok fazla yakıt tüketiminin oluşmasına etken oldu. 1960’tan sonra bazı mimarlar yeniden doğal ışığı temel alan tasarımlar yapmaya başladılar. Günümüz mimarisi yeni bir dönemin başlangıcı oldu ve parametrik tasarım veya akışkan tasarım gibi yeni mimari yaklaşımlar ortaya çıktı. Bu gibi yaklaşımlar mimarların mimarideki sınırları aşmalarına ve farklı biçimlere sahip binalar tasarlamalarına etken oluşturdu. Bu heykelsi tasarımlarda binaların iç mekanlarından daha fazla binaların kabuğu/biçimi ön plana çıkmaya başladı. Değişen bina biçimleri açıklık tasarımlarını ve doğal ışığın iç mekana entegrasyonunun değişimine etken oldu. Açıklıkların işlevsel rolü biricil olarak düşünülürken iç mekana ve kullanıcısına etkisi işlevi kadar tasarım sürecinde yeterince düşünülmedi. Bu çalışma, bu bağlamda, değişen mimari yaklaşımlarla, değişen teknoloji veya malzemelerin de etken olduğu yeni tasarlanan binalarda, açıklıkların tasarımını irdelemektedir. Ayrıca, değişen bina biçimlerindeki açıklık tasarımları sonucunda doğal ışığın iç mekana entegrasyonu ile mekanın tasarımı ve kullanıcının üzerindeki etkisini de tartışır. Anahtar Kelimeler: Doğal Aydınlatma, İç Mekan Tasarımı, İç Mekan, Açıklık Tasarımı, Açıklık Tasarım Teknikleri, İç Mekan Tasarımı Elemanları ve İlkeleri.
Master of Science in Interior Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Interior Architecture, 2014. Supervisor: Assoc. Prof. Dr. Nil Paşaoğluları Şahin.
Keywords: Interior Architecture; Lighting, Architectural and decorative - Design; Light in Architecture; Natural Lighting, Interior Design, Interior Space, Opening and Fenestration Design, Opening Design Techniques, Interior Design Elements and Principles